"Everything Is About Balance": Graduate Education Faculty and the Navigation of Difficult Discourses on Race. Issue 2 (May 2018) - Murray-Johnson, Kayon; Ross-Gordon, Jovita M.
The purpose of this multiple case study was to describe the experiences of graduate education faculty of varying racial/ethnic backgrounds, learning to navigate difficult discourses on race effectively over time. The study employed positionality as a theoretical framework. Findings indicate that faculty balance what we refer to as strategies of self in a bid to work through difficult race talk. In turn, their practice may hold strong potential for influencing a fresh and more holistic approach to engaging in classroom race talk.